Protective activity of an anthocyanin-rich extract from bilberries and blackcurrants on acute acetaminophen-induced hepatotoxicity in rats. Issue 24 (16th December 2016) - Cristani, M.; Speciale, A.; Mancari, F.; Arcoraci, T.; Ferrari, D.; Fratantonio, D.; Saija, A.; Cimino, F.; Trombetta, D.
Abstract: Acetaminophen (N-acetyl-p-aminophenol, APAP) overdosage can produce fatal centrilobular hepatic necrosis in humans. The present study attempted to investigate the protective effect of an anthocyanin-rich extract from bilberries and blackcurrants (AE) against APAP-induced acute hepatic damage in rats. Treatment with AE normalised blood activities of glutamate oxaloacetate and glutamate pyruvate transaminase and prevented APAP-induced plasmatic and tissutal alterations in biomarkers of oxidative stress, probably due to various bioproperties of the components of the extract. Abstract :